Biodegradable materials as foundry moulding sands binders - K. Major - Gabryś (Metalurgija, 2015)
The aim of this article is to show the possibility of using biodegradable materials as part of the composition of foundry moulding and core sand binders. Research shows that moulding sands with biodegradable materials selected as binders are not only less toxic but are also better suited to mechanical reclamation than moulding sands with phenol-furfuryl resin. The use of biodegradable materials as additives to typical synthetic resins can result in their decreased toxicity and improved ability to reclamation as well as in accelerated biodegradation of binding material leftovers of mechanical reclamation.